Polar Experiment Station of VIR: the northernmost outpost of potato research - S. N. Travina (Труды по прикладной ботанике, генетике и селекции)
The establishment and progress of potato cultivation in the Kola Peninsula are closely associated with the Polar Experiment Station of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). The data are presented on the development of early-ripening and high-yielding potato cultivars based on the source material from the VIR collection: ‘Imandra’, ‘Sestra Imandry’, ‘Murmansky’, ‘Snezhinka No. 3’, ‘Khibinsky ranny’, etc. Prominent breeders and scientists, who worked at different times at the Polar Station, contributed to the release of unique early-ripening potato cultivars: J. H. Eichfeld, M. N. Veselovskaya, I. A. Veselovsky, F. I. Manykov, M. A. Vavilova, N. N. Ivanova, L. A. Dremlyug, A. M. Kozeletskaya, S. A. Anikina, G. D. Melnichuk, etc. Some of the cultivars developed from 1937 to 1968 are still used in large-scale potato production in Murmansk Province. Every year the cultivar and species diversity of potatoes is planted in the fields of the Arctic North. Today, the extensive material from the potato collection makes it possible to study the impact of environmental factors, identify sources of earliness and productivity, and conduct breeding activities aimed at the release of early cultivars.